Histórias (e)ditadas: um arquivo que se quer memória - Moreira, Maria Rachel Fiúza (2019)
This thesis is based on the theoretical and methodological assumptions of the Discourse Analysis (DA), an Interpretation discipline that works in the articulation of Linguistics, Historical Materialism, and Psychoanalysis or, as put by Eni Orlandi (2000), in the inset. Our research analyzes the effects of meanings that are present in Memory Globo website, concerning the archives of Jornal Nacional (JN), of the Rede Globo de Televisão.The Jornal Nacional (JN) was the first nationally televised newscast in Brazil, starting on September 1, 1969, and is the longest-running on Brazilian TV, besides being the most-watched journalistic content program. What interests us above all, in this thesis, are questions that point out positions on the discursive surfaces, which compose the so-called “memory” of the JN, involving the main news events in each decade, from 1970 to 2010. In the various links of the file, statements present the selected reports (videos), to compose the program's memory in five decades. Our investigative process looks at the past - memory/archive -, which insists on being kept/presented to society. In this sense, we mainly seek in Pêcheux (2006, 2009, 2010, 2014), Courtine (2003, 2006, 2009), and Orlandi (1992, 2000, 2012, 2014) the bases to understand these concepts and categories, thinking about the archive and memory from a discursive perspective, always considering its historical, cultural, political, and ideological character. In our analysis, we seek to understand the operations that underlie the preparation of the archive; we observed what was selected, which, from the company's point of view, deserved to be highlighted amid so many events.We understand that a file is biased, despite being affected by a chronological view as a succession of facts, and not just a cold database designed by subjects who announce themselves as editors of stories that have already been shown on the news, furthermore, we believe that one should not take the file as evidence. The discourses, when circulating in society, bring to memory other accounts, previously stated, in other places, in other circumstances, mobilizing instantaneous circles of integration of socio-political organizations. Thus, we understand that the website Memoria Globo/Jornal Nacional, through selective gestures, circulates meanings from an ideological position, which, in a memory process, ends up erasing the historical memory. Moreover, it silences, at the same time, its political-corporative position.